Potensi Akomodasi dalam Menunjang Pengembangan Pariwisata di Kabupaten Lahat - Permatasari, Mustika (Politeknik Pariwisata Medan, 2023)
The real sector is one of those places with huge tourist potential and natural resources. Each tourist activity was taken, a hotel became very much needed, since the original stopover from a trip to a tourist destination. The number of accommodations already enabled the number of incoming tourists. But the number of accommodations has not reached a target in accommodating living rooms so the purpose of this research is to know the potential and importance of accommodation in the lrest district. The type of research that is used is a qualitative kind of research and as for the data-collection techniques done by the way a questionnaire does an interview and a questionnaire. Whereas the technical data analysis used is using swot analysis (strength, fatigue, oppotunities and threats). Based on the above research, potential accommodation in supporting tourism development in the district will greatly contribute to meeting the needs of the visiting tourists as well as the development of tourism in the Lahat district.